The Interrelationship of Menopause and Type 2 Diabetes Mellitus - Tejal Lathia; Sanjay Kalra (Diabetes Research, 2020)
Menopause is a critical time in a woman’s life which heralds the cessation of reproductive competence. There is body fat redistribution which increases the risk of type 2 diabetes mellitus (T2DM). There is a complex interrelationship between menopause and T2DM; several variables like the timing of the menopause, the type of menopause and the symptomatology impact this relationship. The treatment of vasomotor symptoms with hormone replacement therapy may also impact glycemia both in women with and without pre-existing T2DM. We tried to examine this relationship based on current scientific evidence. We also suggested strategies to reduce the burden of T2DM in menopausal women.